Pengaruh Media Promosi Brand Ambassador terhadap Keputusan Pembelian Lip Product Barenbliss pada Mahasiswa Tata Rias Universitas Negeri Jakarta - Nadya Shafa Athaya; Mari Okatini Armandari; Dwi Atmanto (Journal on Education, 2025)
Currently, the growth of the cosmetics industry in Indonesia is increasing quite rapidly, one of the companies in the cosmetics industry that can survive and compete in the market is Barenbliss by using one of the promotional media, namely the use of brand ambassadors. The purpose of this study is to find out whether there is an influence between the use of brand ambassador promotional media on the decision to purchase Barenbliss lip products. This research is of a quantitative type, the data collection technique uses a questionnaire and sample determination using the nonprobability sampling method, namely the respondents are students of the Cosmetology Study Program, State University of Jakarta batch 2020, 2021, 2022, and 2023 who have purchased Barenbliss lip products. The results of the study showed that the results of the simple linear regression test were known to be Fcal of 0.590 with a significance value of 0.00. Therefore, the variable of brand ambassador promotion media (X) can be said to have a significant influence on the variable of the purchase decision of Barenbliss (Y) lip product. And also the result of the determination coefficient of 0.414 which means that the influence of the brand ambassador promotion media variable on the Barenbliss lip product purchase decision variable is 41.4%.